Decodificación lectora en estudiantes de segundo grado de primaria de instituciones educativas del Callao - Cock Castro de Amico, Milagros (2012)
This research is descriptive, simple, aimed at evaluating the reading decode of students in the second grade of Educational Institutions of Callao. The variable was measured through the Battery Assessment Processes Readers, Revised PROLEC-R proposed by Cuetos and others (2007), validated for this research by six experts, with a reliability of Cronbach's alpha of 0.807. It also implemented a pilot test on a sample of 110 students, whose results showed a low level in the dimensions of perceptual and lexical processes in reading. The conclusion is that students have difficulties in acquiring the reading process and have a good development to successfully deal with reading comprehension.